La maternidad subrogada en ecuador: impactos de la falta de regulación en la explotación y coerción económica de mujeres vulnerables - Perachimba Parra, Marisela Elizabeth (2025)
Surrogate motherhood is considered a procedure in which a woman, called “surrogate mother” rents her womb and gives birth to a baby for the so-called “surrogate parents” who are people or couples who cannot or decide not to get pregnant, in most cases women who perform this activity do it in exchange for money because they are vulnerable women of low income, who resort to this procedure to obtain a source of income. It should be clarified that surrogate pregnancy is an assisted reproduction technique that can be carried out through in vitro fertilization or artificial insemination. This procedure originated in Philadelphia and is currently practiced in various parts of the world. The objective of this research is to analyze how the lack of norms regulating surrogate pregnancy in Ecuador contributes to the exploitation and economic coercion of women in contexts of socioeconomic vulnerability. For the development of this scientific article, the inductive, analytical, synthetic and legal analytical method was used; the technique chosen was interviews to obtain real and accurate data. With the results obtained, it was possible to determine that in Ecuador there is no law regulating surrogate pregnancy, which contributes to the exploitation and economic coercion of low-income women who are recruited by intermediary agencies. For this reason, it was determined that, in order to cover and diminish the impact of this practice, the application of public policies aimed at dealing with surrogate motherhood is suggested.